Molecular Dynamics Simulations on the Mesophilic Enzyme Vibrio Cholerae Endonuclease I: Salt Effect Study - Djamila Benrezkallah (Chemistry Proceedings)
Some of the most extensively studied marine or estuarine bacteria belong to the genus Vibrio, with Vibrio cholerae being the most notorious species as it is the cause of cholera in humans. V. cholerae is found in tropical and temperate areas and can be classified as a mesophilic bacterium with its growth optimum at around 37 °C. One of the important factors in the activity and stability of each enzyme is its physiological environment. A previous study on the secreted mesophilic enzyme Endonuclease I from the Vibrio cholerae genus (VcEndA) showed that its activity was strongly dependent not only on temperature but also on NaCl concentration. Here, we report a structural study on the mesophilic enzyme (VcEndA) using molecular dynamics simulations at different salt concentrations (NaCl). The analysis of molecular dynamic simulation trajectories reveals that the enzyme is not tolerant and not sensitive to salt since the profile of the rmsf as a function of different concentrations does not show a large difference in the mobility of the enzyme for high values of the NaCl concentration (450 and 650 mM). However, the most flexible regions of the enzyme are recorded under the concentration of 175 mM, which coincides well with the previous experimental work.